Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-01T08:29:32+01:00
Rozwiązania;
a)ax-b=c
ax = c + b /:a
x = (c + b)/a -> założenie: a =/= 0 bo mianownik nie może być zerem

b)2ax-b=2x+c
2ax - 2x = c + b
x(2a - 2) = c + b
x = (c + b) / (2a - 2) -> założenie: a=/= 1 bo wówczas mianownik byłby 0
c)ax+bc=dx+e
ax - dx = e + bc
x(a - d) = e + bc
x = (e + bc) / (a - d) -> założenie: a - d =/= 0
d)2(a-x)+x=b(3-x)
2a - 2x + x = 3b - bx
-x + bx = 3b - 2a
x(-1 + b) = 3b - 2a
x = (3b - 2a) / (b - 1) -> zał.: b różne od 1

4 4 4